Peningkatan Kesadaran Kebersihan Melalui Program Bank Sampah “Tarhilala” Kepada Anak Sekolah Dasar Di Desa Parparean 1 - Yolanda Maria Nababan; Samsa Tamara Lumban Gaol; Josua Kristian Sidabutar; Bartolomeus Sihombing; Nael Fransen Sagala; Parsaoran Silalahi (CV. Multi Kreasi Media, 2025)
Waste is material that is wasted or discarded from natural processes and sources of human activity that has no economic value. Tarhilala Waste Bank is one of the communities in Toba Regency, which means “feels the benefits” of worthless waste, but sorted and deposited in the waste bank becomes quite useful because of the barter system, where waste can be exchanged for basic necessities. Trash bins are infrastructure that is useful for separating waste according to its basic material, so it can indirectly help students to maintain environmental cleanliness and dispose of waste according to its type. The purpose of this activity is to find out what Tarhilala Garbage Bank and KPPM 48 Students of HKBP Nommensen University Medan did to increase the awareness of SD N 173635 Parparean students in disposing of waste according to its type and maintaining environmental cleanliness. Based on this activity, it can be concluded that the socialization of Tarhilala Waste Bank and KPPM 48 Students of HKBP Nommensen Medan University at SD N 173635 Parparean is good, it can be seen from students who dispose of waste according to their type.